2020
DOI: 10.1021/acs.joc.0c01926
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-Recycling Wittig Reaction: Design and Facile Synthesis of a Fluorous Phosphine and Its Reusable Process in the Wittig Reaction

Abstract: This study shows that phosphorus sources can be recycled using the appropriate fluorous phosphine in the Wittig reaction. The designed fluorous phosphine, which has an ethylene spacer between its phosphorus atom and the perfluoroalkyl group, was synthesized from air-stable phosphine reagents. The synthesized phosphine can be used for the Wittig reaction process to obtain various alkenes in adequate yields and stereoselectivity. The concomitantly formed fluorous phosphine oxide was extracted from the reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…All the reactions were run in duplicate. The spectra of all the products obtained were in agreement with the data reported in the literature (see Supplementary Materials ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Methodssupporting
confidence: 88%
“…All the reactions were run in duplicate. The spectra of all the products obtained were in agreement with the data reported in the literature (see Supplementary Materials ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Methodssupporting
confidence: 88%
“…Since the percentage of fluorine atoms in 3 aa is relatively high, we tested the use of aqueous-fluorous biphasic extraction for its isolation (Scheme 5). [27] We found that the combination of S2 in the ESI. † The reaction profile of the addition of 1 a to 1-phenylpropyne was calculated at the M06-2X/6-311 + G(d,p) level using CH 2 Cl 2 as the solvent (Figure 1).…”
Section: Resultsmentioning
confidence: 88%
“…Since the percentage of fluorine atoms in 3 aa is relatively high, we tested the use of aqueous–fluorous biphasic extraction for its isolation (Scheme 5). [27] We found that the combination of Novec‐7100 or 7300 with aqueous methanol provided a suitable solvent system. After biphasic extraction, the desired product was obtained in 82 % yield.…”
Section: Resultsmentioning
confidence: 90%
“…Further derivatives could be converted into a variety of synthetically useful functional groups . Traditional synthesis methods for multisubstituted alkenes include the Wittig reaction, Horner-Wadsworth-Emmons (HWE) reaction, and Peterson olefination . These types of reactions may require harsh conditions or pretreatment of the reactants.…”
mentioning
confidence: 99%